2022
DOI: 10.3389/fnins.2022.977376
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanism of andrographolide activation

Abstract: Andrographolide is a natural antibiotic that has the ability to dispel heat, detoxify, reduce inflammation, and relieve pain. Recent research has shown that it can exert anti-inflammatory effects via multiple pathways and multiple targets (mediated by NF-κB, JAK/STAT, T cell receptor, and other signaling pathways). It can inhibit human lung cancer cells, colon cancer cells, osteosarcoma cells, and other tumor cells, as well as reduce bacterial virulence and inhibit virus-induced cell apoptosis. It can also reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Angiogenesis is the process of germination from existing blood vessels to form new ones, which plays a crucial role in the carcinogenesis of lung adenocarcinoma ( Wang Y. et al, 2019 ). Numerous studies have shown the prognostic value of ARGs in cancer ( Zheng et al, 2021 ; Cai et al, 2022 ; Tao et al, 2022 ), where Sun et al found that POSTN may ultimately affect the prognosis of patients with LUAD by altering the immune microenvironment ( Sun et al, 2022 ), and in our study, 55 ARGs associated with LUAD were obtained from 549 samples in the TCGA database. In addition, we also identified LUAD-related DE-lncRNAs and obtained 50 LUAD-related DE-lncRNAs.…”
Section: Discussionmentioning
confidence: 62%
“…Angiogenesis is the process of germination from existing blood vessels to form new ones, which plays a crucial role in the carcinogenesis of lung adenocarcinoma ( Wang Y. et al, 2019 ). Numerous studies have shown the prognostic value of ARGs in cancer ( Zheng et al, 2021 ; Cai et al, 2022 ; Tao et al, 2022 ), where Sun et al found that POSTN may ultimately affect the prognosis of patients with LUAD by altering the immune microenvironment ( Sun et al, 2022 ), and in our study, 55 ARGs associated with LUAD were obtained from 549 samples in the TCGA database. In addition, we also identified LUAD-related DE-lncRNAs and obtained 50 LUAD-related DE-lncRNAs.…”
Section: Discussionmentioning
confidence: 62%
“…Hederoside C P. koreana MG-63, U2OS [100] Salidroside Rhodiola rosea L. U2OS, MG-63 [101] Tubocapsenolide A Tubocapsicum anomalum SHP-2 [102] Andrographolide Andrographis paniculata U2OS [103] Pacilitaxel Taxus wallichiana var. chinensis (Pilger) Florin U2OS, MG-63 [104] Resveratrol Veratrum album MNNG/HOS, MG-63 [105] β-caryophyllene Dianthus chinensis L. MG-63 [106] Sodium cantharidate Mylabris phalerata Pallas MG-63 [107] Tanshinone I Salvia miltiorrhiza Bunge U2OS, MOS-J [108,109] Notch pathway Cinobufagin Bufo raddei U2OS, MG-63 [110] Curcumin Curcuma longa L. U2OS [92,111] Cannabinoids Cannabis sativa L. MG-63 [112] Dihydroartemisinin Artemisia caruifolia Buch.-Ham.…”
Section: Mg-63mentioning
confidence: 99%
“…Zhu et al [102] found that agrimonia lactone activated the phosphatase activity of Src homology 2 phosphatase 2 (SHP-2), thereby inhibiting the JAK/STAT3 signaling pathway, helping to inhibit the proliferation of OS cells and promote the apoptosis of OS cells. Andrographolide has the effects of clearing heat and detoxicatin, reducing inflammation and relieving pain, while Cai et al [103] found that this compound could reduce the phosphorylation level of STAT1/2 by inhibiting the activity of JAK2/STAT3 signaling pathway, reduce the release of pro-inflammatory cytokines or mediators (including TNF-α, IL-6, IL-1βand IL-10), so as to reduce the degree of paw swelling in mice, and block the progression of OS. Zhang et al [104] found that paclitaxel could inhibit OS cell growth as well as induce OS cell apoptosis by mediating the SHP-1/JAK2/STAT3 signaling pathway, so as to delay the progression of OS to some extent.…”
Section: Treatment Of Os By Jak/stat3 Signaling Pathway With Tcm Inte...mentioning
confidence: 99%
“…ex Nees] (AG) is a natural antibiotic and the main active component of Andrographis paniculata. It can remove heat, expel toxins, relieve inflammation and pain, and effectively treat inflammatory diseases [104]. AG shows a wide range of biological activities, which has been a hot research field for many years [105].…”
Section: Andrographolidementioning
confidence: 99%